Towards a biocompatible artificial lung: Covalent functionalization of poly(4-methylpent-1-ene) (TPX) with cRGD pentapeptide - Möller, Lena; Hess, Christian; Paleček, Jiří; Su, Yi; Haverich, Axel; Kirschning, Andreas; Dräger, Gerald (Beilstein Journal of Organic Chemistry, 2013)
Covalent multistep coating of poly(methylpentene), the membrane material in lung ventilators, by using a copper-free “click” approach with a modified cyclic RGD peptide, leads to a highly biocompatible poly(methylpentene) surface. The resulting modified membrane preserves the required excellent gas-flow properties while being densely seeded with lung endothelial cells.
Keywords: click chemistry; growth factor; nitrenes; plasma chemistry; poly(4-methylpent-1-ene); surface modification